2013
DOI: 10.7567/jjap.52.08jf05
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Sensitivity Tuning of Vertical InN Nanopyramid-Based Photodetectors

Abstract: In this paper, we report on the fabrication of InN nanopyramid-based photodetectors operating within the telecommunication wavelength range. We found that the spectral sensitivity of individually addressable InN nanopyramids can be tuned within an interval of 1550–1750 nm since the band edge luminescence energy correlates with the structure size. According to this, we optimized the nanopatterning technique of SiO2/GaN/sapphire substrates as well as the selective area growth to precisely control the nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition to the InN material quality improvement, the device architecture can be modified to utilize the special characteristics of InN. One of them is the n+/N heterojunction photodetector [9,10,57], which can avoid the bad surface of p-GaN, and many groups have reported encouraging results in the past. The combination of such material systems should be promising for the future generation of nitride-based optoelectronic devices because of the unique long-wavelength capability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the InN material quality improvement, the device architecture can be modified to utilize the special characteristics of InN. One of them is the n+/N heterojunction photodetector [9,10,57], which can avoid the bad surface of p-GaN, and many groups have reported encouraging results in the past. The combination of such material systems should be promising for the future generation of nitride-based optoelectronic devices because of the unique long-wavelength capability.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nitride−based alloys, such as AlN, GaN and InN, have achieved great success in the applications of optoelectronic devices such as light emitting diodes [1,2], lasers [3][4][5], solar cells [6][7][8], and photodetectors [9][10][11][12]. One of the key features about this nitride-based materials is the direct bandgap energy covering from 0.7 eV (for InN) to 6.2 eV (for AlN), and thus provides wide range of absorption from ultraviolet to infrared [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the optimization of the HSQ/SiO 2 isolation procedure was carried out. 38,39 DC measurements indicate that the leakage currents in our device layout reached values typically in the range of 8 pA to 20 pA/cm 2 at 5 V bias voltage-the bias level to be used later for nano-LED and direct electro-optic pumping operation. In the following, micro-electroluminescence measurements were performed at 5 V bias on selectively contacted nano-LED structures integrated into the vertical device layout.…”
mentioning
confidence: 88%
“…Additionally, the ability to successfully achieve photocurrent when illuminated under reverse bias is a promising result towards achieving EL. While several studies using various growth techniques have shown results with InN photodetectors, none of these studies created a p-n junction photodiode consisting of entirely epitaxially grown nitride material 82,[87][88][89][90][91] . One study fabricated a photodetector using MOCVD grown self-assembled InN QDs in a Schottky-like photodetector device, where the InN QDs were protected with a layer of undoped LT GaN 82 .…”
Section: Photodetectorsmentioning
confidence: 99%